Türkiye’de yeni emek denetim ve kontrol alanı: Kalkınma ajansları - (:unkn) unknown (My University, 2012)
1980’li yıllarla birlikte Türkiye’de yerel sermaye gruplarının uluslar arası piyasalara hızlı entegrasyon sağlama güdüsü, Türkiye’nin gelişen ekonomiler arasında yükselme arzusu, ulus altı yerel/bölgesel alanların rekabet edebilirliğini sağlayacak düzenlemeleri hayata geçirmeye başlamıştır. Esnek istihdam politikaları, bölgesel asgari ücret tartışmaları, hizmet ve sanayi sektörel yığışmasının sağlandığı organize sanayi bölgeleri, teknoloji bölgeleri, teknoparklar vs. aktifleştirilirken ademi merkezi yönetimin içerdiği yerel yönetimler yasalarının değiştirilme çabası ve Kalkınma Ajansların kuruluşu farklılaşmayı belgelemektedir. Bu çalışmada sınıf eksenli bakış açısıyla yeni dönemin, yeni ittifaklarını ve işbirliklerini, aynı zamanda yeni gerilim ve çatışma alanlarının olası sonuçları incelenmeye çalışılacaktır.

Since 1980s both the motivation of local capitalists in Turkey for a faster integraton into international markets and the will of Turkish economy to have a superior position in the list of advanced capitalist economies have given a start to the regulations to provide a higher level of competitiveness to local and regional actors. While flexible employment policies, debates on the necessity for a regional minimum wage scheme, organized industry regions (OIRs) which provide sector-specific clustering for services and industrial branches of activities, technology regions, techno-parks and etc. have been activated on one hand some serious efforts to amend legislation on local administrations and to launch Development Agencies on the other have proved above mentioned differentiation. This study aims to make an analysis based on social classes on both the new alliances
A New domain for controlling and supervising labour in Turkey: Development agencies
Keywords: Uluslararası İlişkiler; Kamu Yönetimi